From Perceived Organizational Support to Employee Creativity: Mediating Role of Affective Commitment - Rahmani, Mujeeb Rahman; Muzafary, Sayed Sami; Noorzad, Mohammad Farid (Journal of Social Sciences and Humanities, 2026)
Employee creativity is important for innovation and performance in organizations, but how this creativity is encouraged in higher education institutions is not well understood. This study examines the relationship between perceived organizational support (POS) and employee creativity, with affective commitment as a mediating factor. Drawing on Social Exchange Theory and Organizational Support Theory, the research examines how supportive organizational practices increase emotional attachment among academic staff and encourage creative behavior. A quantitative, cross-sectional research design was used to collect data from 200 academic staff at Kabul Polytechnic University through a structured paper-and-pencil questionnaire. Stratified sampling ensured representation across departments and academic ranks. Descriptive statistics, correlation analysis, and mediation analysis using PROCESS Macro Model 4 in SPSS were performed to test the hypothesized model. The findings show that POS is a significant predictor of employee creativity. That affective commitment partially mediates this relationship, suggesting that organizational support influences creative behaviors both directly and indirectly through strengthening academic staff's emotional attachment to the university. This study contributes to the literature by showing how affective commitment serves as a mediator in the relationship between POS and employee creativity. The findings provide actionable insights for university administrators and policymakers in developing-country contexts and underscore the importance of fostering supportive organizational practices to enhance faculty members' creativity and innovation.